Nutrition Labelling’s Impact on Consumption Patterns and Nutrition Awareness in Community: A Literature Review - Wahyuni, Tri; Flora, Rostika; Rahmiwati, Anita (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Background: Nutrition labelling on food packaging has become an essential tool for assisting consumers in making healthier food choices. Various label styles are used in different nations, but their usefulness varies according to the design and ease of understanding by customers, the aim of this study is to determine the impact of nutrition labels on consumption pattern and nutrition awareness; Methods: This study used a descriptive literature review with 2 data sources, namely PubMed and Google Scholar. The keywords used are